2006
DOI: 10.1097/01.yct.0000244237.79672.74
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Patients and Relatives About Electroconvulsive Therapy

Abstract: The results of the study highlight the complex issues and contradictions in the process of providing information and obtaining consent for ECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
1
27
0
2
Order By: Relevance
“…Our results are consistent with previous findings. 4,12,15,20 In our sample, 67.1% of patients and 77.1% of relatives thought that effectiveness of ECT was not permanent. One reason may be the rare use of continuation ECT to prevent relapse.…”
Section: Patients' and Relatives' Experiencementioning
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with previous findings. 4,12,15,20 In our sample, 67.1% of patients and 77.1% of relatives thought that effectiveness of ECT was not permanent. One reason may be the rare use of continuation ECT to prevent relapse.…”
Section: Patients' and Relatives' Experiencementioning
confidence: 92%
“…4,9Y15, 20 We found that relatives were more satisfied with ECT than patients were. A similar finding had been reported by Tang et al 15 Kerr et al 23 reported that patients had a more favorable attitude toward ECT than relatives, whereas Szuba et al 9 found no difference between the attitudes of patients and relatives.…”
Section: Patients' and Relatives' Attitudesmentioning
confidence: 94%
See 1 more Smart Citation
“…Attitude toward ECT and satisfaction with it seem to be associated with patients' and families' further compliance with this kind of treatment. 17,19 It may even play a role in their adherence to further psychiatric interventions as a whole. As an effective treatment modality, ECT deserves to be appropriately introduced to psychiatric patients who may benefit from it and to their families.…”
mentioning
confidence: 98%
“…While most literature has focused on negative ECT experiences, some research does document positive patient accounts (Chakrabarti et al, 2010;Rajkumar, Saravanan, & Jacob, 2006), and some heterogeneity (Rose, Fleischmann, Wykes, Leese, & Bindman, 2003). We could not find any research that specifically attempted to interpret and connect these disparate accounts.…”
Section: Introductionmentioning
confidence: 47%